Modesty versus Shame: Identity Building through Nature, Personal History and Culture - Filoni, Rosaria (Bioenergetic Analysis, 2019)
The author addresses the subject of modesty, firstly by referring to an article by Alexander Lowen (IIBA Newsletter, 1994), and then an article by Umberto Galimberti, a philosopher and Jungian analyst. Lowen speaks of modesty as «natural pride”, as the expression of the degree of self-perception and self-esteem of the person. It denotes the individual’s ability to contain their feelings and therefore indicates their ability to hold a strong sexual charge. For Galimberti, the human being – who has both a body and individuality – «modesty” expresses the contrasting dialectic between the ego and their animal condition, the two dimensions that intimately constitute the person and tear him or her apart. Each dimension, in fact, hosts two subjectivities. One subjectivity that says «I”, with which we usually identify ourselves, and the other that establishes us as «officials of the species” ensuring its continuity. According to Galimberti, modesty does not limit sexuality but identifies it. The author then reflects on the social and historical aspects of modesty in Italy over the last 50 years.